Surfactant Protein D Is a Biomarker of Acute Respiratory Distress Syndrome - V. V. Moroz; A. M. Golubev; A. N. Kuzovlev; V. M Pisarev; A. K. Shabanov; M. A. Golubev (Общая реаниматология)
Acute respiratory distress syndrome (ARDS) is one of the major problems of reanimatology. Current technologies allow diagnosis of early-stage ARDS. At the same time, no objective parameters for assessing structural damage to the air-blood barrier are available. Biomarkers are promising in this respect. Objective: to estimate the informative value of the plasma and bronchoalveolar lavage (BAL) fluid levels of surfactant protein D (SP-D) as a candidate biomarker for early-stage ARDS. Subjects and methods. A multicenter observational study was conducted at the Clinics of the V. A. Negovsky Research Institute of General Reanimatology (RIGR), Russian Academy of Medical Sciences (RAMS), in 2010—2012. It enrolled 70 patients in accordance with inclusion and exclusion criteria and 30 healthy donors. ARDS and its stages were diagnosed using the criteria developed by the RIGR, RAMS. Blood and BAL SP-D levels were measured by the enzyme immunoassay Human Surfactant Protein D ELISA, RD194059101, BioVendor, USA. Statistical analysis of the findings was performed using a Statistica 7.0 package. ROC analysis was made to determine the sensitivity and specificity of SP-D. The difference was considered significant at pResults. During all study days (1, 3, 5, and 7), the plasma SP-D levels were significantly higher in the patients with ARDS than in those without this condition. On the same study days, these were significantly lower in patients with Stage 1 ARDS than in those with its Stage 2. On the same study days, the plasma SP-D content was significantly higher in deceased patients with ARDS than in survivors with this condition. The SP-D level of >115.8 ng/ml on study day 1 had a sensitivity of 82.5% and a specificity of 80.0% in diagnosing ARDS (area under the curve 0.87; 95% confidence interval 0.778-0.984; p=0.0026). That of Conclusion. The plasma SP-D level of >115.8 ng/ml is a sensitive and specific biomarker °f ARDS and that °f Key words: acute respiratory distress syndrome, surfactant protein D, biomarker, diagnosis, sepsis.